Resonance frequency analysis – indicator of post-implantation morphology of mandibular bone tissue - A. P. Oshurko; I. Yu. Oliinyk; N. B. Kuzniak; L. M. Herasym (Сучасні медичні технології)
This article describes the role of resonance frequency analysis (RFA) as an indicator of the quality of primary implant stability, which is the basis of the goal and confirmed by the results of a clinical case – odontological implantation on edentulous segments of atrophied bone tissue on the right side of the mandible, taking into account the topographic features of its canal, using ultra-short (h = 5.5 mm) implants.